Impact of Memory Problems Post-stroke on Patients and Their Family Carers: A Qualitative Study - Tang, Eugene Y. H.; Price, Christopher; Stephan, Blossom C. M.; Robinson, Louise; Exley, Catherine (Frontiers in Medicine, 2020)
Background Memory problems post-stroke are common and for some, these problems could then progress to a dementia illness. Once in the community, stroke-survivors are looked after by their family doctors although there is evidence that these patients may struggle to access appropriate help in the community for these problems. Although a stroke-survivor may be physically capable of performing daily tasks, they and their families have may learn to manage and adapt to their new memory deficits. There is often less focus on cognitive recovery post-stroke from clinical services perhaps because of the lack of awareness and evidence of these adaptations. The aim of this qualitative study was to report the impact of memory problems on the stroke-survivor and their family once they are living in the community. Methods Semi-structured interviews were conducted with patients and family carers to gain an in-depth understanding of their experiences. Participants were invited to take part in an interview at around six and 12-months post-stroke. A topic guide was developed to explore participant’s care experiences post-stroke when they have also presented with memory difficulties. Data collection and analysis were iterative; all transcripts were anonymised. The data were thematically analysed. Results Twenty-two interviews were conducted. Five family carers and ten stroke-survivors were interviewed at six-months post-stroke, of these eight stroke-survivors and four family carers agreed to a 12-month follow-up interview. They identified several areas of impact: 1) Impact on daily life 2) Emotional impact; and, 3) Compensating strategies Implemented in response to impact. Conclusion Living with stroke combined with memory impairment can have negative effects on the stroke-survivor and their family once in the community. Health professionals and services in the community in particular need to recognise the burden of managing symptoms post-stroke for these individuals and their families. Understanding the impact can enable more effective community and specialist support to be provided particularly if we were to also identify those who may then be at risk of a future dementia illness.